Measuring creativity. Proceedings for the conference "Can creativity be measured?", Brussels, May 28-29, 2009. EUR 24033 EN (Luxembourg, 2009)
"This book collects contributions from the conference that took place in Brussels 28 and 29 of May 2009: "Can creativity be measured?" organized by DG Education and Culture (DG EAC) together with the Centre for Research on Lifelong Learning (CRELL) of the DG Joint Research Centre (DG JRC). The book provides an overview of two main approaches to the measurement of creativity. Firstly, aggregate level approaches, where different existing statistical indicators can be used as pointers of creativity in a region or a nation. Secondly, it explores some aspects in the measurement of creativity at the individual level. The conference constituted the first step in the challenge of measuring creativity in an international, comparative way. If we want to foster creativity we need to measure it. Without the adequate tools to monitor whether or not the policies in place are actually raising the capacity to be creative, there is no way to know that the policies are effective. The main conclusion of the conference is that despite its complexity, creativity can be measured. Still, further work is needed to ascertain what aspects of creativity should be measured and for what purpose. This can only be achieved through consensus among all the relevant stakeholders. The European Year of Creativity and Innovation has been instrumental in the promotion and awareness of the importance of creativity for both economic and social causes. This provides a window of opportunity to establish a clear political and research agenda for the coming years. Europe has a privileged position for building upon its creative capacity; because of the enormous heterogeneity of Europe, there is a tremendous potential for exchanging ideas and enhancing possibilities for creative accomplishments."